2020
DOI: 10.1021/acs.nanolett.9b04718
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Barrier Discharge Applicator for Heating Carbon Nanotube-Loaded Interfaces and Enhancing 3D-Printed Bond Strength

Abstract: Material extrusion (ME) 3D printing is a revolutionary technique for manufacturing thermoplastic parts; however, the printed parts typically suffer from poor interlayer bonding, which causes weak tensile strength in the build direction. Many methods have been proposed to address the mechanical deficiencies of 3D-printed parts, but most fall short of a production-ready solution. Here we report the use of a dielectric barrier discharge (DBD) plasma electrode mounted concentrically around the nozzle of an ME 3D p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…[59][60][61][62] Some of these concepts have seen translation from academic labs to industry. 5 RF heating has demonstrated potential for rapid manufacturing applications for heating bulk materials or targeted parts of the specimens through volumetric or targeted heating. 22,24,25 Major questions surrounding this phenomena remain open.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61][62] Some of these concepts have seen translation from academic labs to industry. 5 RF heating has demonstrated potential for rapid manufacturing applications for heating bulk materials or targeted parts of the specimens through volumetric or targeted heating. 22,24,25 Major questions surrounding this phenomena remain open.…”
Section: Discussionmentioning
confidence: 99%
“…2 In recent years, methods of advanced manufacturing that require rapid heating or targeted heating of components have been developed. 3 These include Joule or resistive heating, [4][5][6][7] induction heating, 8 vibrational heating, 9 ultrasonic heating and welding, 10 infrared heating, 11 and electromagnetic heating. 12,13 Specically, electromagnetic heating is a rapidly emerging eld that has several advantages including rapid, non-contact, non-invasive, and material-selective volumetric heating.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously shown that carbon nanomaterials heat up rapidly in response to RF fields. [5,7,[22][23][24][25][26][27] This phenomenon has already been utilized in manufacturing settings such as interlayer adhesion in 3D-printed thermoplastics, [5] bonding thermoplastic surfaces together, [26] curing preceramic polymer composites, [25] reduction of graphene oxide, [23] and processing of thermosetting prepregs. [27] Carbon nanotubes (CNTs) show excellent RF response, heating up rapidly, and reaching high temperatures easily.…”
Section: Doi: 101002/adem202101351mentioning
confidence: 99%
“…[4] The ability to 3D print these multilayered structures would allow for the free-form fabrication of complex geometries, eliminating the additional cost of ovens and specific molds for each part. Additive manufacturing has been extensively used to 3D print thermoplastics [5][6][7] and metals. [8][9][10] A development of such an on-demand, rapid production technique could facilitate a distributed manufacturing economy for high-performance composites.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] Polymers are widely used in these 3D printing techniques, in which layer-by-layer deposition is always performed to create 3D polymer objects. [12][13][14] However, the layer-by-layer processing DOI: 10.1002/marc.202200053 results in weak interlayer bonding or adhesion between layers, [15][16][17][18] resulting in the anisotropic mechanical properties of the printed products.…”
Section: Introductionmentioning
confidence: 99%